Is Allison More Likely Than Lakisha to Receive a Callback From Counseling Professionals? A Racism Audit Study. (November 2016) - Shin, Richard Q.; Smith, Lance C.; Welch, Jamie C.; Ezeofor, Ijeoma
Using an audit study, we examined racially biased callback responses in the mental health field by leaving voicemails soliciting services with practicing counselors and psychologists ( N = 371). To manipulate perceived race, an actor identified herself with either a stereotypically Black- or non–Latino White-sounding name. Although the difference in callback rate between the two names was not significant, the difference in voice messages from therapists that either promoted potential services or impeded services was significant. The caller with the stereotypically White-sounding name received voice messages that promoted the potential for services at a 12% higher rate than the caller with the stereotypically Black-sounding name. Limitations, future directions for research, and counseling implications are discussed.